Exploring Emotional Triggers in Advertising: A Study of Consumer Buying Behavior in Kathmandu Valley - Sharma, Sandeep; Basyal, Devid Kumar; Lawaju, Purnima; Thakur, Abhishek; Bhandari, Anil; Paudel, Udaya Raj (Journal of Innovation in Academia, 2024)
This study aims to analyze the impact of emotional advertising on consumer buying behavior in Kathmandu Valley. An explanatory research approach is used for the study, employing convenience sampling under the non-probability sampling technique. To gather information from 412 respondents, structured questions and the KOBO toolbox are used. For data analysis, both descriptive and inferential analyses are employed. Findings reveal that emotions such as happiness, excitement, and humor are powerful tools in advertising. They help build trust, shape consumer perceptions, and influence buying behavior. However, challenges such as the gap between promises and delivery and the lack of creativity can hinder the effectiveness of emotional ads. To overcome these challenges, realistic advertisements that showcase the product accurately and creative approaches should be utilized to create a stronger impact on consumers’ purchasing decisions.